Bioavailability of Al, Fe, Mn and Zn in a Decommissioned Mining Area Evaluated by Biomonitoring and Passive Samplers: Robustness, Efficiency and Relationships Between Biotic and Abiotic Monitoring Approaches - Lima, Guilherme dos Santos [UNESP]; Eismann, Carlos Eduardo [UNESP]; Elias, Lucas Pellegrini [UNESP]; Moreira, Luiz Felipe Pompeu Prado [UNESP]; Menegario, Amauri Antonio [UNESP] (Springer Nature, 2025)
In situ assessment of metal bioavailability is crucial for evaluating the degree of contamination in aquatic systems. This study evaluated the bioavailability of Al, Fe, Mn and Zn in water from three sites in a decommissioned mining area near the city of Poços de Caldas (State of Minas Gerais, Brazil). A multi-tool approach was used, combining DGT, transplanted fish (Oreochromis niloticus) and water samples (total and dissolved metal concentration analyses). Samples were taken at 14, 28 and 42-day intervals. Livers, gills and muscles of transplanted fish were analyzed after acid digestion in microwaves and determined by ICP-OES. Significant increases in transplanted fish for Mn and Zn concentrations were observed in the gills. Total and dissolved concentrations showed large fluctuations, possibly influenced by factors such as the rainy season, pH changes, and varying effluent discharges at each sampling point. The concentration of the element measured by DGT devices, proved to be an effective indicator of temporal and spatial variations in the bioavailable levels of Al, Fe, Mn and Zn across all sites analyzed. However, the weak correlations between the different monitoring methods highlight their complementary nature, as each approach captures distinct aspects of metal bioavailability. This underscores the importance of integrating multiple methodologies to provide a more comprehensive understanding of metal dynamics in complex environmental scenarios.